Spatial transformation mechanism of city networks in the middle and lower Ganga Plain in modern times: a perspective on cultural routes - Xihui Wang; Wei Dong; Yicun Pang; Hang Yin (Journal of Asian Architecture and Building Engineering)
The urban system in the middle and lower Ganga Plain experienced a critical spatial transition period from a traditional to modern pattern between the 18th and 19th centuries, developing a network structure influenced by cultural routes. In this study, the historical dimension of city network theory is considered, and a set of quantitative methods to reveal network structure is explored. First, spatial data are extracted from historical maps with equal scales to establish a historical geographic information system (HGIS) database of regional city networks. Second, the spatial‒statistical data translation (S-SDT) method is adopted to construct a gravity model on the basis of a quality evaluation system for historical towns, and the social network analysis (SNA) method is used to analyse the structure of city networks in different historical periods at both the overall and subnet levels. Finally, the centrifugal force and centripetal force associated with cultural routes are used to explain the driving forces and transformation mechanism of city networks in the middle and lower Ganga Plain in modern times. The research results indicate that the rise and fall of interregional cultural routes significantly contributed to the transformation of city networks from a polycentric structure to an eccentric structure.